2002
DOI: 10.1007/s00122-001-0770-7
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-marker for the CMS1 inducing cytoplasm in chives derived from recombination events affecting the mitochondrial gene atp9

Abstract: The complete coding and 3;-flanking region of the mitochondrial gene atp9 of chives ( Allium schoenoprasum L.) was determined in order to develop primers that allow the identification of atp9-related sequences in subsequent PCR-amplifications. One of these sequences is of a chimerical nature, consisting of atp9-homologous regions on its end, interrupted by an insertion that is composed of one atp6-homologous part and one part of unknown origin. This PCR-fragment is 762 bp in size and exclusively amplified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The previously known sequence of the CMS 1 configuration ended in a region homologous to atp 9 (see Introduction; Engelke and Tatlioglu 2002). However, extension of the 3¢-region by 3¢RACE showed that the atp 9 homologous portion of the sequence actually ends upstream of the transcript termini.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The previously known sequence of the CMS 1 configuration ended in a region homologous to atp 9 (see Introduction; Engelke and Tatlioglu 2002). However, extension of the 3¢-region by 3¢RACE showed that the atp 9 homologous portion of the sequence actually ends upstream of the transcript termini.…”
Section: Discussionmentioning
confidence: 97%
“…In the first case the orf would comprise 780 bp, in the latter case 744 bp. The next inframe ATG codon results in the previously described orf 501 (Engelke and Tatlioglu 2002). The predicted proteins encoded by these orf s consist of 260 (29 kDa), 248 (27.5 kDa), and 167 amino acids (19 kDa), respectively, leaving aside possible alterations due to RNA editing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations